Study of Quench and Its Characterization on High Temperature Superconducting Bi-2223/Ag Tape - M Abdollahi Dargah; N Alinezhad; N Abdollahi Ghahi; J Mahmoodi (مجله علوم و فنون هسته‌ای, 2017)
Bi-2223/Ag Superconducting Tape, Local Heat Disturbance, Minimum Quenches Energy, Quench Propagation Velocity, Simulation